New approaches in protecting against atherosclerosis in experimental model of postmenopause - Dalia Medhat, Mona A. El-Bana, Magdi N. Ashour, Ehsan Badawy, Yasser Diab, Jihan Hussein (Journal of Applied Pharmaceutical Science, 2017)
This work is aimed to evaluate the ability of Myrtus communis leaves extract in attenuating endothelial dysfunction as well as risk of atherosclerosis in ovariectomized rats as a common model of postmenopause. Total 60 female albino rats, weighing 180 g were used and assigned to four groups (sham, sham and Myrtus communis leaves extract, ovariectomized rats (OVX) and ovariectomized treated rats with Myrtus communis leaves extract). Plasma estrogen, lipid profile, asymmetric dimethylarginine (ADMA), von Willebrand factor (vWF), interleukin 1beta (IL-1β), Lipoxin A4 (LXA4), aortic oxidant and antioxidant in addition to erythrocyte membrane fatty acids were determined. OVX rats showed a significant increase in inflammatory and oxidant parameters while, Myrtus communis extract administration (100 mg/kg body weight) for two months attenuates these values in treated group. Myrtus communis leaves extract confirmed our idea in protecting from atherosclerosis and endothelial dysfunction in ovariectomized rats due to its high content of anti-oxidant and anti-inflammatory compounds in addition to its high content of ω-3 fatty acids.
Keywords: Myrtus communis leaves extract, ovariectomized rats, estrogen, lipoxin A4, fatty acids, HPLC.